Pembuatan dan Evaluasi Sediaan Masker Gel Peel Off dari Ekstrak Air Mikroalga Spirulina Platensis - Kirani , Zabilla; Putra , Billy Harnaldo; Rahmadasmi, Nola; Fitriani , Oryza Sativa; Nanda , Nanda; Andika, Miming; Hasanah , Rizqa; Haq. AH, Ahdi Dinil; Wulandari , Desti (Journal of Pharmaceutical and Sciences, 2025)
Background: The microalgae Spirulina platensis is a microalgae with numerous benefits, particularly in the fields of health and cosmetics. One of its active compounds, phycocyanin, is a water-soluble antioxidant that is beneficial for facial skincare. A peel-off gel mask is a practical cosmetic product that can be peeled off directly after drying. Objective: This study aimed to develop a peel-off gel mask containing Spirulina platensis water extract and evaluate its physical quality. Methods: The peel-off gel mask was prepared by adding Spirulina platensis water extract at three different concentrations: 0.25% (F1), 0.5% (F2), and 0.75% (F3). Physical quality evaluation included organoleptic testing, homogeneity, viscosity, pH, drying time, adhesiveness, and stability at 4°C and 40°C. A comparison was also made with a commercial spirulina mask product (F4, 0.25%). Results: The physical quality assessment showed that all formulations met the requirements for organoleptic properties, homogeneity, viscosity, pH, drying time, and adhesiveness. In the stability test, the base formula (F0) and F1 (0.25%) were the most stable in terms of organoleptic parameters, while all formulations remained stable in pH. The viscosity of all four formulations remained stable after two months of storage. The commercial mask (F4) exhibited similar physical quality results to F1, with both meeting all requirements. Conclusion: The peel-off gel mask containing Spirulina platensis water extract was successfully developed with satisfactory physical quality. The 0.25% concentration formula (F1) demonstrated good stability, comparable to commercially available products.